The F profile in waters and urine with the levels of T3, T4, Na, K, Ca and P in serum of Morkaraman and Tuj sheep present around Kars province - Kaya, Necati; Utlu, Necati; Maraşli, Nalan; Güldür, Tayfun; Maraşli, Şaban (Scientific and Technical Research Council of Turkey, 1996)
In this study T3, T4. Na, K, Ca and P analysis have been done in the sera of 50 Morkaraman and 50 Tuj sheep raised in Kars and surroundings and F analysis have beben done in the urine of the sheep and waters they drank. In the sera Morkaraman Ca was found to be 10.62±1.2 (% mg). P 4.45±0.83 (% mg). Na 317.30±28 (% mg). K 4.2±0.8 (% mg). T3 1.22±0.34 (nmol/L). T4, 87.54±49 (nmol/L) and F in the urine 0.75±0.30 (ppm) and as for the waters they drank 0.115±0.032 (ppm). In the sera of Tuj sheep Ca was found to be 10.12±0.7 (% mg), P 4.32±1.14 (% mg), Na 307.76±31 (% mg). K 4.3±1.5 (% mg). T3 1.57±0.54 (nmol/L). T4 81.36±44 (nmol/L) and F in the urine 0.91±0.70 (ppm). and as for the waters they drank 0.428±0.210 (ppm). The results reached are the normal levels and there was no significant difference statistically between the sera and urine parameters of Morkaraman and Tuj sheep. It has been observed that Morkaraman and Tuj sheep raised Kars, and surroundings have no deficiency of troid function, and as for flour, there is no Fluorosis. Thus, it has been concluded that the lower yield of milk cannot be due to these elements.
Kars ve Yakin Çevresindeki Morkaraman ve Tuj Irki Koyunlarin Serumlarinda T3, T4, Na, K, Ca ve P ile Idrar ve Su Numunelerinde F Profili
Keywords: Ca; K; Morkaraman and Tuj Sheep; Na; P; T3; T4; Urine and Water F